UHPLC-QTOF-MS-based untargeted metabolomics and mineral element analysis insight into the geographical differences of Chrysanthemum morifolium Ramat cv. “Hangbaiju” from different origins - Long, Wanjun; Bai, Xiuyun; Wang, Siyu; Chen, Hengye; Yin, Xiao-Li; Gu, Hui-Wen; Yang, Jian; Fu, Haiyan (Food research international, 2023)
[Display omitted] •Untargeted metabolomics was used to reveal the chemical differences of Hangbaiju.•Influence of soil mineral elements on the content of differential metabolites was investigated.•Relationship between metabolites and mineral elements was explored by chemometric analysis.•Differential metabolites were significantly correlated with mineral elements in planting soils.•This work provides new insights for better understanding geographical differences of Hangbaiju. Chrysanthemum morifolium Ramat cv. “Hangbaiju” (HBJ), known as one of the “eight flavors of Zhejiang”, is commonly used as a classical tea material for both food and medicine over three thousand years in China. The quality of HBJ is closely related to its geographical origins. However, the mechanism underlying the geographical differences of HBJ remains to be elucidated. In this study, an untargeted metabolomic strategy based on UHPLC-QTOF-MS was established to discover the differential metabolites in HBJ samples from four different origins and explore the possible relationship with mineral elements in planting soils by chemometric analysis. Eight compounds were screened and identified as the key differential metabolites in HBJ samples from different origins. Among them, four important pharmacodynamic compounds including L-arginine, rutin, chlorogenic acid and apigenin-7-O-glucoside are the most abundant in HBJ samples from Tongxiang region, which suggests that HBJ planted in Tongxiang has higher medicinal values. Pearson correlation analysis revealed that the contents of soil mineral elements are positively correlated with those of chlorogenic acid, rutin, apigenin-7-O-glucoside in HBJ samples. Furthermore, an interrelationship model based on random forest algorithm was established to successfully predict the contents of differential metabolites in HBJ samples by soil mineral elements. All these results indicated that the contents of differential metabolites in HBJ samples seemed to be affected by soil mineral elements and therefore resulted in the geographical differences of HBJ.